Comportamento do sinal mecanomiográfico em contrações voluntárias e estimuladas eletricamente - Scheeren, Eduardo Mendonça (2011)
Introduction: Mechanomyography (MMG) is used to measure muscle oscillations and electromyography (EMG) is used to study recruitment thresholds of motor units. Both techniques indicate the effect of the phenomena responsible for muscle fatigue during voluntary contractions. There is a technical limitation to use the EMG with the functional electrical stimulation (FES) simultaneously what the MMG can overcome. Objective: to characterize and compare the EMG and MMG signal during voluntary contraction and to verify if is there difference among the MMG signal by FES protocols for health (HI) and spinal cord injury individuals (SCI). Materials and Methods: the subjects were splited in three groups with 10 participants (HI – voluntary contraction; HI – FES; SCI – FES). EMG surface electrodes and triaxial accelerometer were used to acquire the EMG and MMG signals, respectively. The experimental protocol was done in two steps: (a) fatigue protocol with biceps brachii muscle monitored by EMG and MMG (HI) and (b) four fatiguing (lower limb) electrically stimulated contraction profiles (different days) in HI and SCI. The experimental protocol consisted of four contractions, a rest interval of 15 min and four additional contractions. The features used to analyze the EMG and MMG signals were root mean square (RMS) (time domain) and median frequency (frequency domain). Results: the results indicate an increase in the EMG signal amplitude during the muscle fatigue protocol by voluntary contraction while the MMG signal energy decreased. The RMS and median frequency values may be useful as indicators of fatigue in FES protocols for HI and SCI. The FES profile set to 1kHz pulse frequency, 200μs active pulse duration and burst frequency of 50Hz presented the lowest MMG RMS and median frequency values, suggesting less muscle modification. The MMG signal was different between HI and SCI. Conclusions: in both EMG and MMG biceps brachii signals there was frequency attenuation during the fatigue protocol indicating similarity in both signals. The MMG signal was different between HI and SCI in all FES profiles and it is probably due to the difference in the proportion of muscle fiber between the groups.